Edmund Burke - Utley, T. E. (Thomas Edwin), 1921-1988 (Writers and their work., 1957)
It is not often that good oratory makes good literature, but in the case of Edmund Burke (1729-87) the case is otherwise. Burke, an Irishman, had no early advantages of birth or fortune, but from the time of his entry into the House of Commons, under the patronage of Lord Rockingham, in 1965, until his death over thirty years later, he was a dynamic figure in politics. T.E. Utley's study is a notable appraisal of the art of persuasion. Burke's first major.